Fabrication of Millimeter‐Scale, Single‐Crystal One‐Third‐Hydrogenated Graphene with Anisotropic Electronic Properties. Issue 32 (25th June 2018) - Chen, Hui; Bao, De‐Liang; Wang, Dongfei; Que, Yande; Xiao, Wende; Qian, Guojian; Guo, Hui; Sun, Jiatao; Zhang, Yu‐Yang; Du, Shixuan; Pantelides, Sokrates T.; Gao, Hong‐Jun
Abstract: Periodically hydrogenated graphene is predicted to form new kinds of crystalline 2D materials such as graphane, graphone, and 2D C x H y, which exhibit unique electronic properties. Controlled synthesis of periodically hydrogenated graphene is needed for fundamental research and possible electronic applications. Only small patches of such materials have been grown so far, while the experimental fabrication of large‐scale, periodically hydrogenated graphene has remained challenging. In the present work, large‐scale, periodically hydrogenated graphene is fabricated on Ru(0001). The as‐fabricated hydrogenated graphene is highly ordered, with a √3 × √3/R30° period relative to the pristine graphene. As the ratio of hydrogen and carbon is 1:3, the periodically hydrogenated graphene is named "one‐third‐hydrogenated graphene" (OTHG). The area of OTHG is up to 16 mm 2 . Density functional theory calculations demonstrate that the OTHG has two deformed Dirac cones along one high‐symmetry direction and a finite energy gap along the other directions at the Fermi energy, indicating strong anisotropic electrical properties. An efficient method is thus provided to produce large‐scale crystalline functionalized graphene with specially desired properties. Abstract : Periodically hydrogenated graphene is predicted as a new kind of 2D material, which exhibits novel electronic properties. However, the experimental fabrication of large‐scale periodically hydrogenated graphene remains challenging. Using high‐quality graphene/Ru(0001) as a template, single‐crystal one‐third‐hydrogenated graphene (OTHG) with a millimeter‐scale size is successfully fabricated. The OTHG shows uniform √3 × √3/R30° periodicity relative to the pristine graphene and anisotropic electronic properties.